Why do foreign-owned firms pay more? The role of on-the-job training - Holger Görg; Eric Strobl; Frank A. Walsh (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2002)
Foreign-owned firms have consistently been found to pay higher wages than domestic firms to what appear to be equally productive workers in both developed and developing countries alike. Although a number of studies have documented and some attempted to explain this stylized fact, the issue still remains unresolved. In a multi-period bargaining framework we show that if firm specific training is more productive in foreign firms, foreign firm workers will have a steeper wage profile and thus acquire a premium over time. Using a rich employer-employee matched data set for Ghana manufacturing we show that the foreign wage premium is only acquired by workers over time spent in the firm and only by those that receive on the job training, thus providing empirical support for a firm specific human capital acquisition explanation.
Keywords: 330; Lohnniveau; Eigentümerstruktur; Multinationales Unternehmen; Berufsbegleitende Ausbildung; Verarbeitendes Gewerbe; Ghana